Wireless# certification official study guide : - Carpenter, Tom (McGraw-Hill, 2006)
Prepare for the PWO-050 exam as well as understand the basics of many wireless technologies. Learn how to implement, troubleshoot and maintain small and medium sized wireless networks. Get started in a career in wireless IT